Electron transfer dynamics from single near infrared emitting lead sulfide–cadmium sulfide nanocrystals to titanium dioxide. Issue 38 (22nd September 2017) - Zang, Huidong; Routh, Prahlad K.; Meng, Qingping; Cotlet, Mircea
Abstract : Electron transfer is demonstrated between single near infrared emitting nanocrystals of PbS/CdS and titanium dioxide. Abstract : In this study we report the first successful demonstration of electron transfer between single near infrared emitting PbS/CdS nanocrystals and an external acceptor, titanium dioxide (TiO2 ). We demonstrate distance-dependent electron transfer from single nanocrystals to TiO2 and explore the effect of this process on the photoluminescence dynamics of these nanocrystals. Isolated PbS/CdS QDs are found to exhibit blinking dynamics similar to other nanocrystals like CdSe/ZnS; however, their photoluminescence follows a quasi two-state pattern with heterogeneous photoluminescence lifetimes which may be the result of their emission originating from different energy states. Electron transfer of these nanocrystals with an external acceptor inhibits their photoluminescence lifetime heterogeneity and biases their blinking dynamics in a manner similar to that observed for visible emitting CdSe/ZnS nanocrystals undergoing electron transfer with external acceptors. While the present study reconfirms the universality of quantum dot blinking among various types of nanocrystals, it also demonstrates that universality remains valid for the communication of various types of nanocrystals with the exterior world, here pictured as electron transfer with external acceptors.